Analisis Pengaruh Geometrik Jalan Terhadap Potensi Terjadinya Kecelakaan Pada Tikungan Ruas Jl. Lele – Jl. Tingang VI Kota Palangka Raya - Bella Claudia; Murniati; Robby (Jurnal Serambi Engineering, 2024)
According to the Palangka Raya City Spatial Plan for 2019 - 2039, this road is classified as a secondary collector road, a type of undivided two-lane two-way road. Jl.Lele- Jl.Tingang VI has the characteristics of a rather sharp curve, the width of the road body is not the same, it is bumpy and there is a rather large hole in the road. The purpose of writing this thesis is to analyse the geometric condition of the road at the research site to meet the standards of Bina Marga, to analyse the influence of geometric road conditions on the occurrence of accidents, to provide solutions for handling road geometrics to reduce the potential for accidents at the research site. The result of this study is that the road belongs to road class II B and includes flat terrain. In general, the existing conditions of Jl. Lele-Jl. Tingang VI meet the standards of highways and some do not. What does not meet highway standards is the length of the horizontal curve and the lack of complete traffic signs and road equipment. The treatment is carried out by completing road equipment such as the installation of traffic signals, traffic signs, speed limit warning signs, road markings, lighting equipment, safety fences, delineator signs, noise tap